In silico evaluation of cis-dihydroxy-indeno[1,2-d]imidazolones as inhibitors of glycogen synthase kinase-3: synthesis, molecular docking, physicochemical data, ADMET,MD simulation, and DFT calculations - Nahid Mahmoodi; Mohammad Bayat; Davood Gheidari; Zahra Sadeghian (Journal of Saudi Chemical Society)
A new series of cis-dihydroxy-indeno[1,2-d]imidazolone compounds with distinct structures were synthesized to investigate their potential as inhibitors of the Glycogen synthase kinase 3 (GSK-3). The synthesized compounds were thoroughly characterized using IR, Mass, 1H, and 13C NMR, and in silico screening, including molecular docking, DFT studies using the B3LYP/6-31++G(d,p) basis set in the gas phase drug likeness scores, and molecular dynamic simulation studies, was performed to evaluate protein–ligand interactions and determine the stability of the top-ranked conformation. Our results suggested that compound 4 g, among these compounds, has the potential to be a novel GSK-3 inhibitor as an anticancer agent.